Characterization of titanium aluminide alloys synthesized by mechanical alloying technique - Rozman, Mohd Tahar (2015)
One of the method in powder metallurgy namely as mechanical alloying is not only a simple and inexpensive process, but also a promising technique in improving material’s properties. However, the final product is highly depending on the milling parameters and conditions and very sensitive to environmental factors. In this present study, processing of Ti-Al powders by mechanical alloying technique and subsequent heat treatment was performed with the purpose to gain better understanding of their effect on structural and phase formation of the titanium aluminide alloys, and its relationships to physical, thermal and mechanical properties. It was found that, dry milling at an intermediate speed of 300 rpm is the most optimum condition to produce Ti-Al with crystallite size in nano range. Solid state reaction during mechanical alloying resulted in the formation of Ti(Al) solid solution and remarkable reduction of crystallite size as low as 20 nm. In the initial stage of milling, the thermal stability was influenced by the crystallite size refinement, but after prolonged milling, the stability was regulated by alloying degree of powder constituent. The density and micro-hardness value tag along with the crystallite refinement with gradual decreased of densities from 4.1 g/cm3 down to 3.51 g/cm3, while the hardness increased systematically from 43 to 117 HV by milling duration. After the secondary processing step by subsequent heat treatment up to 850 oC, the powder constituent were transform into a new inter-metallic phase of a dominant TiAl3. When the heating temperature was raised to 1000 oC, it transformed into an inter-metallic mixtures varying from TiAl3, γ-TiAl and α2-Ti3Al. The dual phase γ-TiAl + α2-Ti3Al were obtained in powder milled for 80 and 100 h. A remarkable increased in hardness as high as 622 HV were obtained, while the density values were around 3.7 – 3.9 g/cm3. Mechanical alloying technique was proven as an effective method for producing nano-structured Ti-Al powder, where the parameter need to be selected carefully and thoroughly to obtain the optimum crystallite size. The results conclude that physical, thermal and mechanical properties of powder product has high dependency on crystallite size and alloying degree of the powder constituent produce from mechanical alloying technique. However, after heat treatment, the properties of the alloys were influenced by new phases of the powder constituent in turn governs their performance. In order to get a broader picture on the effect of mechanical alloying process on the formation of Ti-Al alloys, optimal heat-treatment conditions to produce a desired microstructure, and the influence of grain growth need to be further studied. In addition, selection of consolidation process should be reconsidered in other to performed additional mechanical test and analysis.